ANALISIS TINJAUAN HUKUM ISLAM TERHADAP PEDAGANG PAKAIAN DALAM PENETAPAN HARGA DI PASAR DEMPO PERMAI KOTA PAGAR ALAM - M. Agus Maryanto; Reni Hariani; Deva Mardalena (Ekonomica Sharia: Jurnal Pemikiran dan Pengembangan Ekonomi Syariah, 2020)
This research aims at asmaterial input for using the systemthe determination of the price of clothing, materials considerations for sellers in pricing according to principles of Islamic lawmaka in the current study, the researchers want to do an analysis of the review of the price of the clothes in the apply in the market based on the Islamic law Scenic Dempo in order not to violate the provisions of Sharia. In this thesis are described and analyzed pricing of clothes made by traders of clothing in the market town of Picturesque Natural Fence Dempo. The research method used is descriptive qualitative methods, i.e., explain, describe, and illustrate the situation, and then analyzed and drawn conclusions. Data collection techniques used by researchers is the observation, documentation and interviews. Based on the results of the analysis, it can be inferred that the traders of clothing in the market town of Picturesque Natural Fence Dempo method using cost-based pricing, and using principles of trade in Islam. Then the pricing practised by traders of clothing in the market town of Picturesque Natural Fence Dempo is in compliance with Islamic law, the profits obtained also according to Islamic law because the benefits of the advantage to the passing of their efforts